Here' what I came up with:

Given: $\displaystyle \angle SRT = \angle STR$; $\displaystyle \angle 3 = \angle 4$

Prove: $\displaystyle \angle 1 = \angle 2$

Statements:

1. $\displaystyle \angle SRT = \angle STR$; $\displaystyle \angle 3 = \angle 4$

2. $\displaystyle \angle 1 + \angle 3 = \angle SRT$; $\displaystyle \angle = 2 + \angle 4 = \angle STR$

3. $\displaystyle \angle 1 + \angle 3 = \angle 2 + \angle 4$

4. $\displaystyle \angle 1 = \angle 2$

Reasoning:

1. Given

2. Angle addition postulate

3. Addition property of equality

4. Substitution

Am I right?